2009
DOI: 10.1158/1541-7786.mcr-08-0314
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the MAL Gene in Breast Cancer Is a Common Event That Predicts Benefit from Adjuvant Chemotherapy

Abstract: Dysregulation of MAL (myelin and lymphocyte protein) has been implicated in several malignancies including esophageal, ovarian, and cervical cancers. The MAL protein functions in apical transport in polarized epithelial cells; therefore, its disruption may lead to loss of organized polarity characteristic of most solid malignancies. Bisulfite sequencing of the MAL promoter CpG island revealed hypermethylation in breast cancer cell lines and 69% of primary tumors analyzed compared with normal breast epithelial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 33 publications
1
53
0
Order By: Relevance
“…These findings agree with predictions made in our previous study (Figure 2a). To date, several studies have reported MAL gene methylation and mRNA-expression patterns in various cancers such as oral, breast, colon, and GC (Lind et al, 2008, Pal et al, 2012, Horne et al, 2009, Buffart et al, 2008. Buffart et al found an association between mRNA-expression levels and the methylation status of the MAL promoter region (Buffart et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These findings agree with predictions made in our previous study (Figure 2a). To date, several studies have reported MAL gene methylation and mRNA-expression patterns in various cancers such as oral, breast, colon, and GC (Lind et al, 2008, Pal et al, 2012, Horne et al, 2009, Buffart et al, 2008. Buffart et al found an association between mRNA-expression levels and the methylation status of the MAL promoter region (Buffart et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…MAL encodes a trans-membrane protein involved in the sorting of proteins for signaling and transport, and therefore is expressed in most types of epithelial cells (22). Epigenetic regulation of MAL in BC has been described and associated with silencing of expression.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of MAL leads to the loss of the polarized phenotype that frequently accompanies the neoplastic transformation process (14). Recent studies have suggested that downregulation of MAL has been associated with a variety of human epithelial malignancies, including esophageal (7), breast (8), ovarian (9) and cervical (15) cancers. For example, Mimori et al showed that overexpression of MAL in esophageal tumors exhibited decreased cellular motility, a G 1 /S transition block and increased levels of apoptosis via the Fas signaling pathway (7).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mimori et al (7) initially found that MAL was highly expressed in normal esophageal epithelia, but silenced in esophageal tumors. Later, inactivation of MAL was shown to be a common event in breast, head and neck, and gastric cancer (8)(9)(10)(11). However, the functional role and mechanistic action of MAL in CRC remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%